Conflict between Intrinsic Leaf Asymmetry and Phyllotaxis in the Resupinate Leaves of Alstroemeria psittacina - Chitwood, Daniel H.; Naylor, Daniel T.; Thammapichai, Paradee; Weeger, Axelle C.; Headland, Lauren R.; Sinha, Neelima R. (Frontiers in Plant Science, 2012)
Spiral phyllotactic patterning is the result of intricate auxin transport relationships in the shoot apical meristem (SAM) that act to place auxin maxima at the future sites of leaf initiation. Inherent to this process is a bias in auxin distribution in leaf primordia, such that increased auxin is found on the descending side of the leaf (towards the older neighbor) compared to the ascending side (towards the younger neighbor), creating phyllotactically-dependent leaf asymmetry. Separate from phyllotactic-dependent asymmetry is handedness in plants—that is, genetically encoded, fixed chirality, such as the twining of certain vines and the torsions induced by microtubule mutations. Here, we perform a morphometric analysis on the resupinate leaves of Alstroemeria psittacina. Interestingly, the twist in leaves always occurs in a single direction, regardless of the phyllotactic direction of the plant. Because of the resupination, leaves in this species possess an inherent handedness. However, this asymmetry is modulated in a phyllotactic-dependent manner, consistent with the known developmental constraints of phyllotaxis upon leaf morphology. This creates the interesting circumstance in A. psittacina that leaves arising from plants with a counter-clockwise phyllotactic direction are 1) more asymmetric, 2) larger, and 3) possess symmetrical shape differences relative to leaves from plants with clockwise phyllotaxis. The mechanism underlying these differences likely involves a developmental delay in clockwise leaves caused by the conflict between the phyllotaxis-dependent asymmetry and asymmetry resulting from resupination. The evolutionary implications of a dimorphic population without a genetic basis for selection to act upon are discussed.